2016
DOI: 10.1021/acs.chemrestox.6b00028
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Microcystins with Thiols Is Reversible: Base-Catalyzed Deconjugation for Chemical Analysis

Abstract: Microcystins are potent cyclic heptapeptide toxins found in many freshwater cyanobacteria. Most microcystins contain an α,β-unsaturated amide that can react with thiol-containing amino acids, peptides, and proteins in vivo and in vitro. While soluble conjugates formed from small peptides can be extracted and analyzed directly by LC-MS, microcystins conjugated to proteins are analyzed after oxidative cleavage of their Adda side chains, but information on which microcystin analogues were present is lost. Observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 45 publications
1
71
0
Order By: Relevance
“…Meissner et al considered that the protein-bound fraction of MC may not need to be included in total toxicity assessment, due to the seemingly irreversibility of MC conjugation. The view is recently challenged in research by Miles and colleagues [38], which discovered that conjugation of MCs with thiols is reversible, with higher pH promoting deconjugation. They also suggested that certain other conditions, including temperature, free/protein-bound MC concentration and pKa values of the thiols present could influence the equilibrium between conjugation and deconjugation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meissner et al considered that the protein-bound fraction of MC may not need to be included in total toxicity assessment, due to the seemingly irreversibility of MC conjugation. The view is recently challenged in research by Miles and colleagues [38], which discovered that conjugation of MCs with thiols is reversible, with higher pH promoting deconjugation. They also suggested that certain other conditions, including temperature, free/protein-bound MC concentration and pKa values of the thiols present could influence the equilibrium between conjugation and deconjugation.…”
Section: Discussionmentioning
confidence: 99%
“…The reversibility could be possible, as the conjugation reaction between an α,β-unsaturated carbonyl of MC and free thiol of the cysteine of specific biomolecules/proteins is a Michael-type addition reaction [39] and several studies have also discovered that some Michael additions of oxygen, nitrogen and sulfur nucleophiles to α,β-unsaturated carbonyls were reversible [40,41,42,43]. Miles et al [38] pointed out that the environmental and toxicological consequences of the reversibility in aquatic organisms need further investigation. A similar view was also presented by Schmidt et al [44] who proposed that more studies on this reversible conjugation are essential for complete understanding of the toxicity, transport and transformation of MC in living cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are >120 cases reported of isomeric MCs reported, significantly limiting the utility of accurate mass measurements alone for MC identification. It should be noted that conjugates between MCs and thiol-containing biomolecules (e.g., cysteine, glutathione) have been reported [81,100,101] and that mass ranges and molecular formula tolerances need to be widened accordingly when characterizing these compounds.…”
Section: Mass Spectrometry For Structural Elucidationmentioning
confidence: 99%
“…Covalently bound toxins may not be biologically available to consumers and/or unable to inhibit protein phosphatases, but proteolytic enzymes in the digestive system could free them from the tissues (Smith et al, 2010). The binding of MCs to protein phosphatases may, to some extent, be reversible (Miles et al, 2016). The consequences of the irreversible binding of MC to protein phosphatases is not well understood (Ibelings and Chorus, 2007;Smith et al, 2010), and conventional extraction methods may not be efficient for quantification of the protein-bound fraction of MCs in biological samples .…”
Section: Lc-ms/ms Gc-ms;mentioning
confidence: 99%
“…The consequences of the irreversible binding of MC to protein phosphatases is not well understood (Ibelings and Chorus, 2007;Smith et al, 2010), and conventional extraction methods may not be efficient for quantification of the protein-bound fraction of MCs in biological samples . Covalently bound MCs are not considered toxic, but if they can be released from proteins under certain conditions, the covalently bound fraction may act as a secondary toxic pool whereby additional toxins can be released back into circulation of the organism (Miles et al, 2016). The 2-methyl-3-methoxy-4-phenylbutyric acid (MMPB) method, targets all MCs with an intact native ADDA residue and in most cases targets both protein and nonprotein bound MCs.…”
Section: Lc-ms/ms Gc-ms;mentioning
confidence: 99%